Assessment of the effectiveness of storage structures for maintaining the quality of maize seed stored at different moisture levels - Marahatta, Santosh (Journal of Agriculture and Natural Resources, 2021)
One of the main causes of food insecurity is the timely unavailability of quality seeds for smallholder farmers in developing countries. Improved storage technologies are effective in reducing storage losses. Thus, the objective of this research is to assess the traditional and emerging seed storage structures/materials for the maintenance of seed qualities. The effect of different storage conditions (moisture content of seed at the time of storage, i.e. 12±0.15% and 13.5±0.18%; storage containers such as metal bin, earthen pot, Purdue Improved Crop Storage (PICS) bag, and jute bag) on seed qualities of maize were assessed. The seed was collected from Chitwan, Nepal and a laboratory experiment was conducted at the central seed testing laboratory, seed quality control center (SQQC), Hariharbhawan, Lalitpur. The experiment was done using a two-factor complete randomized design in a four replicates design. Data regarding the seed qualities (seed moisture percentage, germination percentage, root and shoot length, and vigor index) just before store and also at 45, 90, 135, 180, and 240 days after storage (DAS) was performed as per the standard followed by International Seed Testing Association (ISTA). The germination percentage, root, and shoot length decreased with increasing storage duration. The seed stored in the higher moisture level had significantly higher seed moisture throughout the storage duration. Seed stored in the traditional structures (jute bag and earthen pot) had lower seed moisture at 120 and 180 DAS. The seed stored at lower moisture resulted in a higher germination percentage, long root, and shoot length. Up to six months of storage germination of maize seeds stored in the earthen pots, PICS bag, and Jute bags were statistically similar. The traditional storage structures are equally effective for the maintenance of seed quality of maize.